Assessing Response Rates and Sleep Disorder Prevalence: Insights from a Propranolol Treatment Study for Infantile Haemangiomas - Francesca Opri; Roberta Opri; Marco Zaffanello; Erika Rigotti (MDPI AG, 2024)
Background: Infantile haemangiomas (IHs) sometimes require treatment with propranolol. Sleep disturbances are the most frequently reported side effects. Monitoring adverse drug events necessitates repeated hospital visits, which can be challenging during a pandemic. Objectives: To explore the effectiveness of a new electronic questionnaire in identifying sleep disturbances related to treatment with propranolol and potential confounding factors. To evaluate the response rate to the questionnaire. To report the proportion of patients on propranolol with sleep disturbances. Methods: In an observational, prospective cohort study, caregivers provided clinical information during ambulatory visits and via an electronic questionnaire after an 8-week treatment course with propranolol and at the time of treatment interruption. Adverse drug reaction reporting forms were assessed for causality. Results: The questionnaire response rate was 91%, and the completion rate was 100%. A total of 59% of patients experienced sleep disturbances during propranolol treatment, which were considered adverse reactions. Sleep disorders were frequent during sleep regression phases and in subjects who fell asleep during physical contact with caregivers or bed-sharing with parents. Conclusion: The application of this questionnaire allows for identifying adverse sleep events associated with propranolol in IHs and potential confounders. Counselling on sleep hygiene is recommended before treatment onset.